1993
DOI: 10.1017/s0033291700038861
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory in monozygotic twins discordant for schizophrenia

Abstract: SynopsisLearning and memory were assessed in 24 monozygotic (MZ) pairs of individuals discordant for schizophrenia or delusional disorder and seven normal pairs of MZ twins. On declarative memory tasks, the affected group displayed a pattern that might best be characterized as dysmnesic in that they performed significantly worse than the discordant unaffected group on story recall, paired associated learning, and visual recall of designs, but they learned over time, had relatively preserved recognition memory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
91
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(103 citation statements)
references
References 70 publications
11
91
0
Order By: Relevance
“…A great advantage of this type of task is that the figures to be copied are rather simple and, by mirroring the stimuli, the perceptual and memory load is kept constant. As was to be expected from studies showing that schizophrenia is associated with intact procedural learning (Clare et al, 1993;Goldberg, et al, 1993;Watanabe et al, 2002), the results demonstrated that patients with schizophrenia performed within the normal range when they copied the 'non-conflicting' patterns. However, in copying 'conflicting' patterns patients performed differently compared to the healthy controls.…”
Section: Introductionsupporting
confidence: 80%
“…A great advantage of this type of task is that the figures to be copied are rather simple and, by mirroring the stimuli, the perceptual and memory load is kept constant. As was to be expected from studies showing that schizophrenia is associated with intact procedural learning (Clare et al, 1993;Goldberg, et al, 1993;Watanabe et al, 2002), the results demonstrated that patients with schizophrenia performed within the normal range when they copied the 'non-conflicting' patterns. However, in copying 'conflicting' patterns patients performed differently compared to the healthy controls.…”
Section: Introductionsupporting
confidence: 80%
“…In this study, only the total raw score of the number of correct items from the backward portion of the test is used, since previous studies suggest that the backward span task is a more robust measure of working memory. 17,66 The Trail Making test is a measure of executive functioning and set alternation. 69 Trail A involves connecting numbers in succession, while Trail B requires subjects to connect numbers and letters alternately in successive order.…”
Section: Subjectsmentioning
confidence: 99%
“…12 Schizophrenia patients as well as their unaffected relatives perform poorly on tasks that assess working memory function. [13][14][15][16][17][18][19][20][21][22][23] Working memory is moderately heritable with 43-49% of its variability accounted by genetic factors 24 In a series of studies involving a population isolate, a significant additive genetic heritability estimate was found in verbal working memory, and for visual working memory at a trend level. 20,21,25 Spatial working memory performance was more highly correlated in monozygotic twins than in dizygotic twin pairs.…”
mentioning
confidence: 99%
“…A study that included non-ill relatives with either one or multiple first-degree relatives diagnosed with schizophrenia showed that deficits in story recall scaled with the level of genetic predisposition for the disorder (Faraone et al, 2000). Three twin reports including MZ twin pairs discordant for schizophrenia as well as control twins found that patients performed significantly worse than their co-twins, who performed significantly worse than the healthy twins on a story recall task, suggesting disease-related as well as familial influences on verbal memory performance in schizophrenia (Goldberg et al, 1990;Goldberg et al, 1993;Goldberg et al, 1995). Furthermore, one report showed that patients from concordant pairs did not differ from patients from discordant pairs, suggesting a similar etiology of the observed performance deficits in both groups (Goldberg et al, 1995).…”
Section: Introductionmentioning
confidence: 99%